A prospective study in peritonitis patients to compare the impact of subcutaneous negative suction closure, conventional primary closure of skin and subcutaneous tissue and open skin technique following laparotomy - Mathews, Mano Zac; Subramanyam, Sriram Gopalakrishnaiah; Mitta, Nivedita (International Surgery Journal, 2019)
Background: Abdominal wall closure in the presence of sepsis presents a challenge to the surgeon. The objective of this study is to determine the advantages and disadvantages of each method to individualise the techniques based on patient profile about surgical site infection, duration of hospitalisation and morbidity. Methods: A prospective comparative study was conducted among 102 operated patients of peritonitis in the Department of General Surgery at St John’s Medical College and Hospital. The patients were divided into three groups, group A, group B and group C. In group A, skin and subcutaneous tissue was closed after draining the subcutaneous space by a negative-suction drain. In group B, the patient’s skin and subcutaneous tissues were closed primarily with continuous sutures without negative suction drain. In group C, the laparotomy wound was closed and the skin was left open. And the outcome compared in the form of wound infection, hospital stay and morbidity. Patients on immunosuppressive therapy and paediatric patients were excluded. Demographic and clinical variables were recorded at the time of admission. SPSS version 18 was used for analysis. Results: The study showed male preponderance and the mean age was 43.2 years. Duodenal perforation was the commonest cause of peritonitis in this study (38.2%). Incidence of surgical site infection was less in Group A (20.6%) compared to group B (52.9%) and group C (29.4%). Duration of hospital stay was also less in Group A patients (9.3±3.6 days) compared to other two groups. 37 patients who were included in the study were diabetic, out of which 25 patients (67.6%) developed surgical site infection. Conclusions: It can be concluded from this study that abdominal wall closure using a sub cutaneous negative suction drain in peritonitis cases reduces the incidence of surgical site infection, duration of hospital stays, subsequent surgeries related to wound dehiscence and its associated morbidity.